212 Suppressor of cytokine signalling 3 (socs3) interaction with cavin-1 links socs3 function and cavin-1 stability. (5th June 2017) - Williams, Jamie; Alotaiq, Nasser; Palmer, Tim
Abstract : Caveolae are lipid raft microdomains essential for the compartmentalisation and regulation of several signalling pathways e.g. JAK/STAT signalling. Disruption of caveolae is a significant factor in multiple disorders including muscular dystrophy, cardiovascular disease, and cancer. Central to caveolae stability is cavin-1 which couples caveolae to the microtubule network to prevent degradation of a key structural element i.e. caveolin-1, and caveolae disassembly. Via an unbiased quantitative proteomics screen, we have identified SOCS3, a negative regulator of JAK/STAT signalling, as a novel cavin-1 interactor. SOCS3-cavin-1 interactions were characterised by immunoprecipitation assays and probing overlapping peptide arrays. SOCS3 bound to multiple regions within cavin-1, while a PEST motif within the C-terminal region of the SOCS3 SH2 domain was required for interaction with cavin-1 independently of its capacity to bind phospho-tyrosine. Biochemical analysis and confocal imaging also demonstrated that SOCS3 localisation within lipid raft microdomains and at the plasma membrane required cavin-1. Interestingly, SOCS3 does not ubiquitinate cavin-1 but instead supports cavin-1/caveolae stability. Moreover, genetic deletion of cavin-1 results in the loss of SOCS3-mediatied inhibition of cytokine signalling. Importantly, while the inhibitory function of SOCS3 relies on its induction, caveolae stabilisation occurs at basal SOCS3 expression levels. Thus, transmission electron microscopy demonstrated that SOCS3 knock-out endothelial cells show reduced levels of caveolae. Our data suggest a novel role for SOCS3 in regulating caveolae assembly while cavin-1, acting as a scaffold-protein, might aid SOCS3-dependent regulation of JAK/STAT signalling. This is the first indication of a novel role for SOCS3 in caveola homeostasis and suggests that loss of caveolae represents a novel mechanism by which chronic activation of pro-inflammatory JAK/STAT signalling could be triggered in disease.